Public relations : (McGraw-Hill, 2007)
Coverage of global markets, new technologies, and multiculturalism throughout make this dynamic text the cutting-edge choice for public relations courses. Accompanied by a unique, free DVD with video interviews of leaders in the public relations field, the text presents and explains in a personal, jargon-free style the fundamental tools of public relations practice, providing a multi-disciplinary understanding of the emerging trends within the field